Surface chemistry and spectroscopy of UG8 asphaltene Langmuir film, part 1 - Orbulescu, Jhony (Langmuir : the ACS journal of surfaces and colloids, 2010)
This research focuses on a systematic investigation of UG8 asphaltene Langmuir films at the air-water interface using toluene as the spreading solvent. From the surface pressure-area isotherms, it was concluded that small-sized aggregates are spread on the water surface and the compression of the film leads to formation of large aggregates. Our methods provide a stringent test and confirmation for the formation of corresponding asphaltene nanoaggregates that have recently been proposed for bulk solutions. These results were confirmed by compression-decompression isotherms, Brewster angle microscopy, and p-polarized infrared reflection-absorption spectroscopy. The transfer of a single layer using both the Langmuir-Schaefer and Langmuir-Blodgett deposition techniques shows different aggregate shapes depending on the technique used as imaged using atomic force microscopy. The films reveal the existence of nanoaggregates spread on the water surface that coexist with large aggregates formed during compression. For the nanoaggregate, the thickness of the Langmuir-Schaefer and Langmuir-Blodgett films determined by AFM is consistent with small aggregation numbers of nanoaggregates determined by Langmuir film compression. In addition to these findings, the spreading solvent, toluene, was found to be trapped within the aggregates as confirmed by in situ UV-vis spectroscopy at the air-water interface. This result was possible only after waiting a time period of 1 h to allow the complete evaporation of the spreading solvent. This is the only study that reveals the presence of the in situ toluene within the UG8 aggregates directly at the air-water interface